Smoking Status as a Predictor of Hip Fracture Risk in Postmenopausal Women of Northwest Texas - Marjorie R. Jenkins, MD; Anne V. Denison, RN, MS, CIC (Preventing Chronic Disease, 2008)
IntroductionThe purpose of this study was to determine the effect of cigarette smoking on the risk of hip fracture for postmenopausal women living in rural and urban areas of Northwest Texas.MethodsUsing an unmatched case-control design, we compared postmenopausal women who had recently experienced osteoporotic hip fracture with women who had not. Both study groups completed a questionnaire on demographic, clinical, and behavioral risk factors for osteoporotic hip fracture. We categorized smoking status as never smoked, former smoker, and current smoker. Covariates included age, weight, age at menopause, physical activity, estrogen replacement, calcium supplementation, and rurality. We used univariate and multivariate logistic regressions to test the associations between hip fracture and the independent variables of interest.ResultsWe found an increased risk of hip fracture for former smokers (adjusted odds ratio [OR], 2.27; 95% confidence interval [CI], 1.22–4.21) and current smokers (adjusted OR, 3.72; 95% CI, 1.59–8.70). Residence in a rural county (population <100,000) also was associated with increased risk (adjusted OR, 2.71; 95% CI, 1.48–4.95).ConclusionFormer and current smoking increased the risk of hip fracture in this population of postmenopausal women.